Hydrodynamic Model of Diver–DPV Coupled Multi-Body and Its Underwater Cruising Numerical Simulation - Hansheng Li; Fenglei Han; Haitao Zhu; Jiawei Zhang; Weipeng Zhang; Yuliang Wu (Journal of Marine Science and Engineering, 2021)
Diver propulsion vehicles (hereinafter referred to as DPV) are a kind of small vehicle with underwater high-speed used by divers, who are able to grasp or ride on, and operate the volume switch to change the speed. Different from unmanned underwater vehicles (UUVs), the interference caused by diver’s posture changing is a unique problem. In this paper, a Diver–DPV multi-body coupling hydrodynamic model considering rigid body dynamics and fluid disturbance is established by analyzing the existing DPV related equipment. The numerical simulation of multi-body articulated motion is realized by using Star-CCM+ overlapping grid and DFBI 6-DOF body motion method. Five cases of DPVs underwater cruising in a straight-line when restraining diver movement is simulated, and five cases with free diver movement are simulated too. Finally, the influence of the diver’s posture changing on the cruising speed resistance is analyzed, and the motion equation including the disturbance is solved. The final conclusion is that, the disturbance is favorable at high speed, which can reduce the cruising resistance, and unfavorable at low speed, which increases the cruising resistance. The friction resistance Ff always accounts for the main part in all speed cases.